2019
DOI: 10.1021/acs.nanolett.9b02312
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Free-Standing Nanosheets of Bi2O2Se: Room Temperature Ferroelectricity in Self-Assembled Charged Layered Heterostructure

Abstract: S2 MethodsReagents. Bismuth nitrate (Bi(NO3)35H2O, Alfa Aesar, 99.9%), selenourea (SeC(NH2)2, Alfa Aesar, 99.9%), potassium hydroxide (KOH, S D Fine-Chem Limited (SDFCL)), sodium hydroxide (NaOH, SDFCL), Disodium EDTA (C10H14O8Na2N2H2O, SDFCL) and ethanol were used without any further purification.Synthesis procedure. 100 mg (0.206 mmol) of Bi(NO3)35H2O, 12.7 mg (0.103 mmol) of SeC(NH2)2 and 306.8 mg (0.824 mmol) of disodium EDTA were sequentially added at a 5 minutes interval into 20 ml water in a glass be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 58 publications
(95 reference statements)
5
124
0
Order By: Relevance
“…Whereas in the low temperature piezoelectric scattering regime, the carrier mobility follows a gentle temperature dependence of μ ~ T −0.47 [26][27][28][29][30] and reveals the intrinsically high mobility. [21,[31][32][33] Consequently, a persistently high PF above 400 µW m −1 K −2 over a wide temperature range (80-200 K) is obtained, which corresponds to high carrier mobility in the piezoelectric scattering regime. The high PF over such a wide temperature range is unusual since the PF for most material has the peak value at a very narrow temperature range corresponding to the materials bandgap.…”
Section: Atomically Thin Bi 2 O 2 Se Has Emerged As a New Member In 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in the low temperature piezoelectric scattering regime, the carrier mobility follows a gentle temperature dependence of μ ~ T −0.47 [26][27][28][29][30] and reveals the intrinsically high mobility. [21,[31][32][33] Consequently, a persistently high PF above 400 µW m −1 K −2 over a wide temperature range (80-200 K) is obtained, which corresponds to high carrier mobility in the piezoelectric scattering regime. The high PF over such a wide temperature range is unusual since the PF for most material has the peak value at a very narrow temperature range corresponding to the materials bandgap.…”
Section: Atomically Thin Bi 2 O 2 Se Has Emerged As a New Member In 2mentioning
confidence: 99%
“…www.advmat.de www.advancedsciencenews.com associated with POP scattering due to the polar nature of ferroelectric Bi 2 O 2 Se flake. [21,32,33] The in-plane (x direction) polarizations of 2D Bi 2 O 2 Se originated from the asymmetric charge transfer in the top Bi-O parallelogram channel. And the strong dipole polarization in the cross-plane (z direction) duo to the high electronegativity of O atom.…”
Section: Atomically Thin Bi 2 O 2 Se Has Emerged As a New Member In 2mentioning
confidence: 99%
“…For instance, 2D ferroelectricity has been demonstrated in CIPS, WTe 2 , In 2 Se 3 , SnS, SnTe, Bi 2 O 2 Se, and 1T‐MoTe 2 . [ 14,54,74,78,82,83,100,162–165 ] Notably, traditional ferroelectric materials are insulator, but researchers proved that 2D ferroelectric materials could be insulators, semiconductors, and metals, which endows them with wider applications in electronic and optoelectronic devices. In this section, the intrinsic ferroelectricity in 2D layered materials is summarized.…”
Section: Ferroelectric Materials and Fe‐gated Heterostructuresmentioning
confidence: 99%
“… 21 Microscopic imaging and controlled manipulation of the out-of-plane polarization in 2D ferroelectric materials via PFM have been demonstrated in MoTe 2 MLs, 2 freestanding perovskite thin films, 22 as well as several-layer thick van der Waals ferroelectrics. 5 , 11 , 13 , 15 17 However, although PFM studies of in-plane ferroelectricity have been reported in several nanometer thick layered materials, 13 15 , 18 20 to the best of our knowledge none of the current PFM studies of in-plane polarized ferroelectrics has reached the thickness limit of a single van der Waals ML.…”
mentioning
confidence: 91%